Assessing Arundo donax L. in vitro-tolerance for phytoremediation purposes. (August 2020) - Cano-Ruiz, J.; Ruiz Galea, M.; Amorós, M.C.; Alonso, J.; Mauri, P.V.; Lobo, M.C.
Abstract: Phytoremediation using high production crops could be an alternative for the recovery of metals polluted soils. In this sense, the Arundo donax L. energy crop has shown tolerance to moderate concentrations of heavy metals. The objective of this work was to test the tolerance of micropropagated plants of Arundo donax to increasing concentrations of cadmium, chromium, cooper, nickel and lead, in an in vitro culture medium. Biomass production and concentration of heavy metal in shoots and roots were analyzed. Results showed that heavy metals were accumulated mostly in subterranean organs. The increase in heavy metal concentration was dose dependent and not always follows a linear relationship. Arundo donax showed a broad tolerance to cadmium (0.5 mM), chromium (0.2 mM), cooper (2 mM), nickel (0.5 mM) and lead (1 mM). In relation to cooper, Arundo donax showed a hyperaccumulative potential. These results suggest the potential use of Arundo donax in the phytomanagement of polluted soils although further studies should be carried out using polluted soils. Highlights: In vitro assays show the tolerance of Arundo donax micropropagated plants to metals. Arundo donax presents high tolerance to cadmium, chromium, cooper, nickel and lead. The highest metal accumulation is observed in subterranean organs. Arundo donax behaves as a Cu hyperaccumulator in the assay conditions. Arundo donax could be used in the phytomanagement of metal polluted soils.